Ensaios em economia da educação - Camargo, Juliana (2017)
The aim of this study is to provide rigorous evidence of the impact of a brazilian vocational education and training program on its beneficiaries. For this, we took advantage of the selection criteria for the program, in which the beneficiaries were selected through a lottery . Besides, our unique dataset allow us to evaluate the effect of the intervention not only on the economic dimension, but also on human capital, socio-emotional, crime and risky behavior outcomes. This is a valuable contribution since there is a lack of evidence in the literature about the impact of VET programs on these outcomes. Our estimations were based on ITT and LATE strategies. Overall, our results indicated that, at least in the short-run, there was no effect of the program on conventional labor market outcomes, such as employment and formal work probability and wages. Also, we found no effect in socio-emotional, crime and risky behavior dimensions. However, our results pointed towards a possible heterogeneity of the program, since we found positive and significant effects of the intervention on women, specially in labor market (formal work probability and wage) and socio-emotional (extraversion) outcomes.